2001
DOI: 10.1123/jtpe.20.2.188
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Three Types of Goal Setting Conditions on Tennis Performance: A Field-Based Study

Abstract: Utilizing a two-stage random sampling technique, this study investigated the effect of three types of goal setting conditions (self-set, instructor-set, and “do your best” control) on tennis serving performance of college students (N = 156) in nine beginning tennis classes. A 3 × 2 × 5 (goal setting conditions × gender × trials) ANCOVA with repeated measures on the last factor and baseline performance as the covariate was computed. A significant interaction of goal setting conditions by trials was revealed (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 22 publications
1
23
0
8
Order By: Relevance
“…Regarding personal goal setting, the present indings provide further support for goal setting theory (Locke & Latham, 1990 corroborating previous indings that goal setting leads to higher sport performance (Kyllo & Landers, 1995;Wanlin et al, 1997;Weinberg et al, 2005) and that this effect is not restricted to assigned goals, but can also be found for self-set goals (e.g., Boyce, Wayda, Johnston, Bunker, & Eliot, 2001;Ward & Carnes, 2002). Moreover, the present indings support claims from researchers working at integrating goal setting theory and achievement goal theory (Latham & Locke, 2007;Seijts et al, 2004) that achievement goals have only an indirect effect on performance and that the effect of achievement goals on performance is mediated by setting speciic goals.…”
Section: Discussionsupporting
confidence: 78%
“…Regarding personal goal setting, the present indings provide further support for goal setting theory (Locke & Latham, 1990 corroborating previous indings that goal setting leads to higher sport performance (Kyllo & Landers, 1995;Wanlin et al, 1997;Weinberg et al, 2005) and that this effect is not restricted to assigned goals, but can also be found for self-set goals (e.g., Boyce, Wayda, Johnston, Bunker, & Eliot, 2001;Ward & Carnes, 2002). Moreover, the present indings support claims from researchers working at integrating goal setting theory and achievement goal theory (Latham & Locke, 2007;Seijts et al, 2004) that achievement goals have only an indirect effect on performance and that the effect of achievement goals on performance is mediated by setting speciic goals.…”
Section: Discussionsupporting
confidence: 78%
“…For example, Boyce (1990) showed the effects of instructorset specific goals versus "do your best" encouragement in rifle shooting in a college physical education class. She later replicated the study in a college tennis setting comparing "do your best" encouragement with self-set goals and instructor-set goals with the same results (Boyce, Wayda, Johnston, Bunker, & Eliot, 2001).…”
Section: Evidenced-based Goal-setting Principlesmentioning
confidence: 79%
“…Promoting skill mastery is important in helping students develop psychomotor skills. In addition, goal-directed practice with feedback enhances learning, and goal setting elicits a better response than suggesting to students that they simply focus on doing their best (Boyce et al, 2001). Establishing goals provides students with a clear objective toward which to focus their efforts.…”
Section: Discussionmentioning
confidence: 94%
“…These are goals that are specific, measurable, attainable, realistic and time related. One study indicated that instructor-set goals and student-set goals were superior to "doing one's best" on a tennis serve (Boyce, Johnston, Wayda, Bunker, & Eliot, 2001). According to energization theory, the goal must be attractive and not too easy or too difficult because the student may lose interest in pursuing the goal (Weinberg & Gould, 2011).…”
Section: The Principlesmentioning
confidence: 98%